PENGARUH METODE PEMBELAJARAN STORYTELLING TERHADAP KEMAMPUAN MENYIMAK SISWA KELAS V SDN 53 SAULEYA KABUPATEN TAKALAR - Sucitra; Akhir, Muhammad; Haslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the storytelling learning method on the listening skills of fifth-grade students at SDN 53 Sauleya in Takalar Regency. This study used a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects were all 30 fifth-grade students at SDN 53 Sauleya. The sampling technique used purposive sampling, consisting of 15 students in the experimental class and 15 students in the control class. Data collection used a listening ability test in the form of a pre-test and post-test. The results showed a significant effect between the use of the storytelling method on students' listening skills. This was demonstrated by an increase in the average score in the experimental class from 66.67 to 87.00. Based on the results of the hypothesis testing using the independent sample t-test, the significance value (Sig. 2-tailed) was less than 0.05, indicating a significant effect. This indicates that the use of storytelling methods can optimally influence students' listening skills. Therefore, the application of engaging learning methods such as storytelling should be considered as an effective strategy in influencing students' listening skills in elementary schools